Analisis Pengaruh Pembiasaan Shalat Berjamaah terhadap Disiplin Belajar Siswa di SMP Berbasis Pesantren - Mochamad Ichsan; Didit Darmawan (ALSYS, 2026)
Low student learning discipline remains one of the main obstacles to achieving academic targets, especially during the critical hours after midday. This study aimed to examine the effect of habituation to congregational Dhuhr prayer on students’ learning discipline at SMP SBP Darul Hikmah Bangkalan. This study employed an associative quantitative approach with simple linear regression analysis. The study population consisted of 244 students, with a sample of 90 students selected through the Proportional Stratified Random Sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with SPSS software. The results showed that habituation to congregational prayer had a positive and significant effect on students’ learning discipline (p < 0.05). The coefficient of determination (R²) value of 0.486 indicated that habituation to congregational prayer contributed 48.6% to the variation in students’ learning discipline. This study concludes that the habituation of ritual worship contributes to the development of independent academic discipline. The implications of this study affirm the importance of strengthening structured religious programs as a behavioral intervention strategy to support the formation of students’ character and intellectual orderliness in Islamic-based educational institutions.